Exploratory studies on chrysin via antioxidant, antimicrobial, ADMET, PASS and molecular docking evaluations - Adedotun F. Adesina; Adewale Adewuyi; Chiagoziem A. Otuechere (Elsevier, 2024)
Introduction: Chrysin, a flavonoid found in Feng Jiao (Chinese name for propolis), exhibits a wide array of pharmacological activities and is recognized for the significant roles it plays in traditional Chinese medicine. The present study aimed to explore the in vitro antioxidant and antimicrobial potentials of chrysin and provide mechanistic insights via in silico experiments. Methods: The in vitro antioxidant and antimicrobial activities of chrysin, a natural flavone found in propolis was investigated. Molecular docking interactions, the Adsorption, Distribution, Metabolism, Elimination and Toxicity (ADMET) and Prediction of Activity Spectra for Substances (PASS) were used to predict the biological activities of chrysin. Results: Chrysin exhibited a considerable 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals scavenging activity and ferric reducing antioxidant capacity. Chrysin demonstrated inhibition against S. typhi, and B. subtilis with lowest MIC value of 1.25 mg/mL which was similar to that of chloramphenicol. Drug-likeness and ADMET study of the two compounds showed their physicochemical properties as non-toxic, non-mutagenic, high permeability, good solubility and absorption characteristics. Discussion: The research below shows that chrysin and silymarin had antioxidant, free radical scavenging, antibacterial, hepatoprotective and anticarcinogenic properties based on PASS prediction of biological activities. Molecular docking of chrysin and silymarin, a standard hepatoprotective drug, with tumour necrosis factor alpha converting enzyme (TACE) and manganese-dependent superoxide dismutase (SOD 2) showed interactions with LEU 401, VAL 402, HIS 405 amino acid residues at the active sites of TACE. Chrysin non-covalently interacted with amino acids of SOD 2 at the active site while silymarin non-covalently interacted at a site different from the active site. Silymarin demonstrated a minimum binding energy of - 9.7 Kcal/mol and - 7.0 Kcal/mol for TACE and SOD 2, respectively while chrysin showed a minimal binding energy of - 9.0 Kcal/mol and - 6.8 Kcal/mol for TACE and SOD2 respectively. Conclusion: The study concluded that chrysin exhibited antioxidant and antimicrobial activity via inhibition and regulation of TACE and SOD2 and possibly offer protection against hepatotoxicity in animal experimental models.